Microcomputer applications - Price, Wilson T. (Chicago : The Dryden Press, 1989)
This textbook. however, isn't just a software manual. It is, rather, a general introduction to computers in business, with a special emphasis on microcomputers and applications software.
Part One. Computers and Microcomputers: an Overview -- Part Two. Processing and Desktop Publishing -- Part Three. Spreadsheets and Computer Graphics -- Part Four. Database Management -- Part Five. Advance Topic.
Includes bibliographical references and index.
Keywords: MICROCOMPUTERS